Collapse of the Atlantic Meridional Overturning Circulation in a Strongly Eddying Ocean‐Only Model - René M. vanWesten; Michael Kliphuis; Henk A. Dijkstra (Geophysical Research Letters)
Abstract A collapse of the Atlantic Meridional Overturning Circulation (AMOC) under a quasi‐equilibrium freshwater forcing has now been found in a hierarchy of ocean‐climate models and up to a fully‐coupled climate model, the Community Earth System Model (CESM). However, the effects of eddies on the ocean flows are represented in a highly idealized way in the CESM and it is unknown how these affect AMOC stability. Here, we show results of the first quasi‐equilibrium hosing simulation with a strongly eddying ocean‐only model in which the AMOC collapses. By comparing these results to those of a companion non‐eddying simulation with the same model, it is found that eddies are able to maintain a weak (∼5 Sv) AMOC flow in the collapsed state. In addition, we find that the AMOC induced freshwater transport at 34°S is a reliable physics‐based early warning indicator for the onset of the AMOC collapse.